Abdominal Hernias, Giant Colon Diverticulum, GIST, Intestinal Pneumatosis, Colon Ischemia, Cold Intussusception, Gallstone Ileus, and Foreign Bodies: Our Experience and Literature Review of Incidental Gastrointestinal MDCT Findings. (30th May 2017) - Di Grezia, G.; Gatta, G.; Rella, R.; Donatello, D.; Falco, G.; Grassi, R.; Grassi, R.
Abstract : Incidental gastrointestinal findings are commonly detected on MDCT exams performed for various medical indications. This review describes the radiological MDCT spectrum of appearances already present in the past literature and in today's experience of several gastrointestinal acute conditions such as abdominal hernia, giant colon diverticulum, GIST, intestinal pneumatosis, colon ischemia, cold intussusception, gallstone ileus, and foreign bodies which can require medical and surgical intervention or clinical follow-up. The clinical presentation of this illness is frequently nonspecific: abdominal pain, distension, nausea, fever, rectal bleeding, vomiting, constipation, or a palpable mass, depending on the disease. A proper differential diagnosis is essential in the assessment of treatment and in this case MDCT exam plays a central rule. We wish that this article will familiarize the radiologist in the diagnosis of this kind of incidental MDCT findings for better orientation of the therapy.